Fundamentals of engineering thermodynamics - Moran, Michael J.; Shapiro, Howard N. (New York : John Wiley and Sons, 2000)
This book is about: INtroductory concepts and definitions; Energy and the first law of thermodynamics; Evaluating properties; Control volume energy analysis; ...
Keywords: Thermodynamics; Thermodynamics